Evaluation of bone marrow in patients with pancytopenia - Pathak, R; Jha, A; Sayami, G (Journal of Pathology of Nepal, 2012)
Background: Pancytopenia is a common hematological finding resulting from varieties of disease processes that require evaluation of bone marrow. This study was carried out to evaluate bone marrow findings in patients presenting with pancytopenia. Materials and Method: This was a prospective cross sectional study carried out to identify the causes of pancytopenia based on bone marrow examination. Bone marrow examinations were performed in 503 cases for different indications over a period of one year. Results: One hundred and two (20.27%) cases fulfilled the criteria of pancytopenia. Trephine biopsy was possible only in 48 cases. In 75% cases aspiration findings were similar to biopsy. Mean age of patients was 38.8 years. Maximum number of cases was seen in age group of 15-30 years. Hypoplastic anemia was the commonest cause followed by hematological malignancies, megaloblastic anemia, leishmaniasis and Gaucher disease. Bone marrow examination alone was able to establish the diagnosis in 76.5% cases. In rest marrow findings were nonspecific and in 4.9% cases findings were normal. Conclusion: Bone marrow aspiration coupled with trephine biopsy can diagnose majority but not all the cases of pancytopenia. Hypoplastic anemia, hematological malignancies and megaloblastic anemia are the commonest causes of pancytopenia. Maximum diagnostic yield can be achieved by correlation with clinical findings, peripheral blood findings and with other laboratory and radiological parameters. Journal of Pathology of Nepal (2012) Vol. 2, 265-271 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6875